2009
DOI: 10.1292/jvms.71.33
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Efficacy of Bruceine A, a Natural Quassinoid Compound Extracted from a Medicinal Plant, Bruced javanica, for Canine Babesiosis

Abstract: ABSTRACT. Bruceine A, a natural quassinoid compound extracted from the dried fruits of Brucea javanica (L.) Merr., was evaluated for its antibabesial activity in vitro and in vivo. Bruceine A inhibited the in vitro growth of Babesia gibsoni in canine erythrocytes at lower concentration compared with the standard antibabesial drug diminazene aceturate and killed the parasites within 24 hr at a concentration of 25 nM. Oral administration of bruceine A at a dosage of 6.4 mg/kg/day for 5 days resulted in no clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 29 publications
(42 reference statements)
1
8
0
2
Order By: Relevance
“…is widely distributed throughout Asia, where the fruits have been used for various ailments, including cancer, amoebic dysentery, and malaria. Quassinoids isolated from this plant had inhibitory activity against not only Plasmodium falciparum [12] but also Babesia gibsoni in vitro [16] and in vivo [11] as well as against T. evansi in vitro [2]. In this study, crude extract from the fruits of B. javanica showed the second strongest activity against T. evansi (IC 50 =27.2  7.9 g/ml) and good selectivity (SI=11.4), confirming the previous studies.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…is widely distributed throughout Asia, where the fruits have been used for various ailments, including cancer, amoebic dysentery, and malaria. Quassinoids isolated from this plant had inhibitory activity against not only Plasmodium falciparum [12] but also Babesia gibsoni in vitro [16] and in vivo [11] as well as against T. evansi in vitro [2]. In this study, crude extract from the fruits of B. javanica showed the second strongest activity against T. evansi (IC 50 =27.2  7.9 g/ml) and good selectivity (SI=11.4), confirming the previous studies.…”
supporting
confidence: 89%
“…Recently, we reported that quassinoids isolated from the fruits of an Asian medicinal plant, Brucea javanica, showed remarkable antibabesial and antitrypanosomal activities [2,11,16], suggesting a promise use of medicinal plant extracts for protozoan diseases in livestock. In the present study, the in vitro antitrypanosomal and cytotoxic activities of crude extracts of medicinal plants in Myanmar were evaluated.…”
mentioning
confidence: 99%
“…Many chemical constituents have been isolated from Brucea genus, including quassinoids, alkaloids, triterpenoids, and flavonoids [2][3][4][5]. Its core components are quassinoids, which possess various biological activities including anti-tumor [4], anti-malarial and anti-babesial [6,7], anti-viral [8], anti-bacterial [9,10] and hyperglycemic [11] activities.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, bruceoside A has good efficacy in leukemia and brusatol amarissima exert significant anti-inflammatory activity. 12 The quassinoids contain bruceine A, B, C, D, E, F, G, H, and I (Figure 2), 13,14 brusatol A, 15 dihydrobrusatol B, 16 bruceoside A, B, C, D, E, F, G, I, J, K, L, P, and S (Figure 3), [17][18][19][20][21][22][23] brusatol amarissima E2-glucosidase, 13 brusatol ketoacid, and bruceen.…”
Section: Chemical Ingredientsmentioning
confidence: 99%